Patients With Common Variable Immunodeficiency (CVID) Show Higher Gut Bacterial Diversity and Levels of Low-Abundance Genes Than the Healthy Housemates - Bosák, Juraj; Lexa, Matej; Fiedorová, Kristýna; Gadara, Darshak C; Micenková, Lenka; Spacil, Zdenek; Litzman, Jiří; Freiberger, Tomáš; Šmajs, David (Frontiers in immunology, 2021)
Common variable immunodeficiency (CVID) is a clinically and genetically heterogeneous disorder with inadequate antibody responses and low levels of immunoglobulins including IgA that is involved in the maintenance of the intestinal homeostasis. In this study, we analyzed the taxonomical and functional metagenome of the fecal microbiota and stool metabolome in a cohort of six CVID patients without gastroenterological symptomatology and their healthy housemates. The fecal microbiome of CVID patients contained higher numbers of bacterial species and altered abundance of thirty-four species. Hungatella hathewayi was frequent in CVID microbiome and absent in controls. Moreover, the CVID metagenome was enriched for low-abundance genes likely encoding nonessential functions, such as bacterial motility and metabolism of aromatic compounds. Metabolomics revealed dysregulation in several metabolic pathways, mostly associated with decreased levels of adenosine in CVID patients. Identified features have been consistently associated with CVID diagnosis across the patients with various immunological characteristics, length of treatment, and age. Taken together, this initial study revealed expansion of bacterial diversity in the host immunodeficient conditions and suggested several bacterial species and metabolites, which have potential to be diagnostic and/or prognostic CVID markers in the future.
Keywords: homeostáza; Biodiversity; adenosin; Feces; Clostridiaceae; metagenom; Dysbiosis; Metabolomics; výpočetní biologie; RNA, Ribosomal, 16S; metabolomika; Hungatella hathewayi; biodiverzita; Homeostasis; Gastrointestinal Microbiome; běžná variabilní imunodeficience; Common Variable Immunodeficiency; střevní mikroflóra; Metagenome; CVID; lidé; metagenome; metabolome; Humans; microbiome; dysbióza; RNA ribozomální 16S; common variable immunodeficiency; Adenosine; feces; Computational Biology